2001
DOI: 10.1007/pl00002214
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotisch-thrombozytopenische Purpura (Moschcowitz-Syndrom)

Abstract: The therapy of choice is plasma exchange against fresh frozen plasma, whereupon the mortality could be dramatically reduced in the past decades. In case of treatment resistance to plasma exchange there exists no common treatment schedule. One therapy option is immunosuppressive treatment with corticosteroids and vincristine. In case of chronic relapsing TTP splenectomy should be discussed. In spite of severe thrombocytopenia substitution of thrombocytes is contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
1
0
7
Order By: Relevance
“…Kadar bolnik nima diareje in koprokulture omenjenih povzročiteljev ne zaznajo, govorimo o atipični obliki HUS. 1 Tudi znotraj TTP razlikujemo med primarno (idiopatska ali dedna) in sekundarno obliko. Sekundarno TTP lahko povzročijo številna bolezenska stanja, kar prikazuje Tabela 1.…”
Section: Uvodunclassified
“…Kadar bolnik nima diareje in koprokulture omenjenih povzročiteljev ne zaznajo, govorimo o atipični obliki HUS. 1 Tudi znotraj TTP razlikujemo med primarno (idiopatska ali dedna) in sekundarno obliko. Sekundarno TTP lahko povzročijo številna bolezenska stanja, kar prikazuje Tabela 1.…”
Section: Uvodunclassified
“…Bei der TTP können aufgrund der verminderten Aktivität der VWF-Spaltungsprotease die ultragroßen VWF-Multimere akkumulieren und zu Thrombozytenaggregation und nachfolgender Mikroangiopathie führen [8]. Der therapeutische Erfolg durch Plasmaaustausch gegen FFP bei der TTP kann durch o.g.…”
Section: Therapie Und Verlaufunclassified
“…Pathomechanismus erklärt werden. Hierdurch werden die großen VWF-Multimere entfernt und deren fehlender Spaltungsprotease zugeführt [8]. Trotz Ähnlichkeiten in der klinischen Präsentation zwischen der TTP und der mikroangiopathischen Hämo-lyse bei Patienten mit metastasierenden Tumoren ist der therapeutische Erfolg der Plasmapherese hier sehr fraglich, da diese mikroangiopathische Hämolyse ohne Verminderung der VWF-Spaltungsprotease-Aktivität einhergehen kann [15].…”
Section: Therapie Und Verlaufunclassified
“…In practice, diagnosis of TTP is often delayed, since less than 40% of pat ients present with the classic pentad of symptoms [13]. Early recognition and rapid initiation of plasmaexchange therapy is essential for reducing mortality and severity of clinical manifestations [4]. Moake et al [14] found unusually large molecular forms of vonWillebrand Factor (vWF) in the plasma ofTTP-patients and propo sed them to have a pathogenic role in the formation of microvascular vWF-and platelet -rich thrombi, which are found in the microcirculation of patients with acute TTP [14,15].…”
Section: Introductionmentioning
confidence: 99%